2015
DOI: 10.21608/jfds.2015.50068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lupine Powder on Rheological, Chemical and Microbiological Properties of Yoghurt

Abstract: The effect of different concentrations (2, 4, 6 and 8%) of lupine powder on sensory, rheological, chemical and microbiological properties of yoghurt samples were investigated during refrigerated storage at 4°C for 15 days. The results indicated that the overall pH of lupine yoghurt lowered with increasing of % lupine powder as well as acidity increased gradually by adding lupine powder. The development of acidity in yoghurt (control) or which supplemented with lupine was increased gradually during storage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
8
6
0
Order By: Relevance
“…These results were in agreement with Abdel‐Salam et al. (2015) who showed that the increase of lupine powder caused a decrease in the pH of lupine yoghurt treatments. Generally, changes in acidity followed the opposite pattern as pH changes, with higher acidity in SLP treatments and a small proportional rise during storage, which could be due to the growth and activity of bacterial strains present in the Labneh matrix, as well as the enzymatic activities that convert lactose to the resultant organic acid.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in agreement with Abdel‐Salam et al. (2015) who showed that the increase of lupine powder caused a decrease in the pH of lupine yoghurt treatments. Generally, changes in acidity followed the opposite pattern as pH changes, with higher acidity in SLP treatments and a small proportional rise during storage, which could be due to the growth and activity of bacterial strains present in the Labneh matrix, as well as the enzymatic activities that convert lactose to the resultant organic acid.…”
Section: Resultssupporting
confidence: 93%
“…The health benefits of lupines are enormous, including reducing appetite, regulating blood sugar levels, lowering blood pressure, lowering cholesterol levels and improving bowel health. After 30 days of consuming lupine beans, blood pressure, triglycerides and cholesterol levels will be reduced, as well as weight loss (Abdel‐Salam et al., 2015). Lupines are members of the Fabaceae, Geniteae and Leguminosae families (Pastor et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lupin is a grain crop with excellent nutritional value and stands out for its high protein content [ 28 , 29 , 30 , 31 ]. Moreover, it has both health and commercial value in the food industry, and is rich in phytochemicals (such as polyphenols, phytosterols, squalene) [ 25 , 28 , 29 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current use of lupin whole seed as a food is limited to local dietary habits, and lupin products are mainly produced for people with special dietary needs: Athlete nourishment and various products dedicated to celiac individuals, vegans, and vegetarians [ 4 , 36 ]. Lupin seeds are often consumed as an appetizer, furthermore they can be milled into flour and used for the manufacturing of baked goods and pastry products [ 31 , 35 ]. Moreover, lupin could be used for production dairy additives and dairy substitutes such as plant milk and yogurt [ 16 , 33 , 34 , 35 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the application of Lupine in dairy field; Shalaby et al (2013) prepared functional whipped cream by partial replacement (10%) of milk fat with different combinations of Sweet Lupine Flour (SLF) and Whey Protein Concentrate. While, Abdel-Salam et al (2015) manufactured Zabadi with different concentrations (2, 4, 6 and 8%) of SLF and studied the effect of this addition on chemical, rheological, sensory, and microbiological properties of Zabadi samples.…”
Section: Introductionmentioning
confidence: 99%